Dmrt2 promotes transition of endochondral bone formation by linking Sox9 and Runx2 - Koichiro Ono (Nature Portfolio, 2021)
Koichiro Ono et al. report that Dmrt2 is a critical transcription factor for chondrocyte maturation during endochondral ossification. The study shows that Dmrt2 is the direct target of Sox9 and acts as a transcriptional coactivator of Runx2 providing novel insights into the transcription factor network during skeletal development.